Effect of the diluent on the solvent extraction of neodymium(III) by bis(2-ethylhexyl)phosphoric acid (D2EHPA) - Batchu, Nagaphani Kumar; Binnemans, Koen (Hydrometallurgy, 2018)
The effect of different types of diluents on the extraction of neodymium(III) from a chloride aqueous feed solution by the acidic extractant bis(2-ethylhexylphosphoric) acid (D2EHPA) was investigated. A total of 11 aliphatic, mixed aliphatic-aromatic and aromatic diluents were considered. D2EHPA was very well miscible with all diluents, even at 90% (v/v) of extractant. Aliphatic diluents gave the highest extraction efficiencies, while aromatic diluents did suppress the formation of emulsions or gels. Although a good separation of Dy(III) over Nd(III) was observed at 0.5 mol/L D2EHPA in all diluents, aromatic diluents were found to yield the highest separation factors. This study shows that the effect of the diluent on the extraction behaviour of Nd(III) is primarily determined by the aliphatic/aromatic content of the diluent. Diluents with the same concentration of aromatics show very similar behaviour. The choice of a diluent can be based on factors other than the extraction behaviour, for instance price and volatility. •Distribution ratios are higher in aliphatic diluents than in aromatic diluents.•Extraction behaviour was largely defined by the aromatic content of the diluent.•Nature of diluent does not have significant influence on the equilibration time.•Good Dy(III)/Nd(III) separation was observed at 0.5 mol/L D2EHPA in all diluents.•Aromatics in the diluent suppress gel formation